Hidden disaster - Bongers, Erik; European Commission. Humanitarian Aid Office (Luxembourg : Publications Office of the European Union, 2010)
On back of t.p.: "a wholly fictitious story written to illustrate how the European Commission's Humanitarian Aid department responds to crisis, from a human interest angle"
"KR-31-09-144-EN-C" on page [4] of cover
doi: 10.2795//11166
Keywords: Humanitarian assistance -- European Union countries -- Comic books, strips, etc; International relief -- European Union countries -- Comic books, strips, etc